A Soft Bionic Pectoral Fin Actuated by a Series of Differential Gear Units - Chaowu Sheng; Liwen Nan; Qiaoling Gao; Jiawang Chen; Peng Zhou; Han Ge; Haocai Huang (Journal of Marine Science and Engineering, 2026)
The bionic pectoral fin serves as the primary propulsion component of ray-inspired robots. In our previous research, a motion equation was proposed for the real pectoral fin, which can be modeled as a series of NACA airfoil-shaped cross-sections distributed along the spanwise direction. Each cross-section undergoes two coupled rotational motions about its chord line and spanwise rotational axis. To achieve this type of motion, this article introduces a novel bionic pectoral fin mechanism driven by a series of differential gear units. The differential unit generates two coupled rotational motions corresponding to the cross-section of the pectoral fin in motion. A series of interconnected differential units provides a unique topology for the bionic mechanism and can generate a diverse range of motions. Through kinematic analysis, the motion equation was mapped onto the rotational angles of motors in the differential units. The proposed bionic mechanism was then fabricated and subjected to experimental test, demonstrating its effectiveness with a maximum thrust of 0.71 N. The distinctive structure of this bionic mechanism differentiates it from conventional designs and is expected to provide some inspiration for bionic pectoral fins and ray-inspired robots.